New chromosome counts and evolutionary tendencies in some dicots analyzed from Parvati Valley, Kullu district, Himachal Pradesh. Issue 3 (3rd July 2018) - Gupta, Himshikha; Kumar, Rohit; Gupta, Raghbir Chand; Singhal, Vijay Kumar
ABSTRACT: The present study covers chromosome counts, male meiosis and pollen fertility in 164 species of dicots from the Parvati Valley, Kullu district, Himachal Pradesh. Gathered cytological information generates first ever chromosome counts, new diploid/polyploid cytotypes and varied chromosome counts. As many as 41 species (25%) showed intraspecific euploid cytotypes. Role of aneuploidy causing chromosomal variation is apparent from the existence of 71 species (43.29%) depicting aneuploid/dysploid cytotypes at diploid and/or polyploid levels and 114 genera showing dibasic/polybasic nature. The existence of abnormalities in several species resulted in the production of genetically imbalanced and sterile pollen grains. The viable gametes with variable chromosome numbers might have played a part in the origin of aneuploids, polyploids and species complexes. Also the non-viable gametes produced as a consequence of meiotic irregularities might have resulted in reduction of reproductive success of species through seeds. Consequently, the plants have adopted alternate means of propagation through asexual and vegetative modes which is quite prevalent in the plants of area.